2D-HSQC-NMR-Based Screening of Feruloylated Side-Chains of Cereal Grain Arabinoxylans - Schendel, Rachel R.; Bunzel, Mirko (Frontiers in Plant Science, 2022)
Arabinoxylans of commelinid monocots are characterized by high contents of ferulic acid that is incorporated into arabinose-bearing side-chains of varying complexity. Species-related differences in the feruloylated side-chain profiles of grain arabinoxylans are observed and lead to differences in arabinoxylan functionality. Here, a semi-quantitative assay based on 1H-13C-correlation NMR spectroscopy (HSQC experiment) was developed to profile feruloylated side-chains of cereal grain arabinoxylans. Following acidic liberation of the feruloylated side-chains from the xylan backbone and a clean-up step using C18 solid phase extraction, the feruloylated oligosaccharides FA (5-O-trans-feruloyl-L-arabinofuranose), FAX (β-D-xylopyranosyl-(1→2)-5-O-trans-feruloyl-L-arabinofuranose) and FAXG (α-L-galactopyranosyl-(1→2)-β-D-xylopyranosyl-(1→2)-5-O-trans-feruloyl-L-arabinofuranose) were analyzed by HSQC-NMR. Marker signals were identified for each compound, and experimental conditions such as solvent and internal standard as well as measurement and processing conditions were optimized for a semi-quantitative determination. The approach was validated with respect to accuracy, precision, limit of detection, and limit of quantification. The newly developed approach was applied to several cereal samples including oats, popcorn maize, wheat, and wild rice. Data were compared to an LC-MS approach published earlier by our group, demonstrating that the results of the HSQC approach were comparable to the more time-consuming and technically more challenging LC-MS method.